Um recorte do cenário da Psicologia Organizacional no Espírito Santo - Santos, Flávia de Melo dos (2013)
This research is proposed to investigate the look of eleven psychologist in the Espírito Santo State, about the Organizational Psychology, specifically professional working in big organizations located in this State. Specifically, it was possible to distinguish that four of them working in industries, four working in Service Company, and three working in human resource consulting companies. We utilize as a proposal methodology a qualitative vision, because we suppose that the qualitative research allow us to apprehend the multiplicity of human conditions and the world of the work. Assert in this search an actuation from the Organizational Psychologist that modifies with the changes of the world business, and therefore, appoint many ways with different movements in the Espírito Santo State.